The effective-compound compatibility of JHF inhibits fibroblast activation in pulmonary fibrosis by enhancing PINK1/PARK2-mediated mitophagy - Yunping Bai; Xiaohong Yin; Qin Zhang; Xingjie Sang; Wenjing Wu; Dong Shao; Peng Zhao; Jiansheng Li (Scientific Reports)
Abstract This work aimed to elucidate the anti-PF mechanism of ECC-JHF.The effects of ECC-JHF on lung fibrosis and fibroblast activation were investigated by establishing a BLM-induced PF rat model and a transforming growth factor-beta (TGF-β)-induced fibroblast activation model. Furthermore, the effects of ECC-JHF on Nrf2 signaling and mitophagy were explored both in vivo and in vitro. In the PF model rats, ECC-JHF mitigated pathological damage, reduced collagen deposition, decreased levels of malondialdehyde (MDA) and P62, and increased levels of total superoxide dismutase (T-SOD) as well as the expression of Nrf2, HO-1, PINK1, PARK2, and LC3B in lung tissues. These results suggest that the anti-PF mechanism of ECC-JHF may be associated with the inhibition of oxidative stress and the enhancement of mitophagy. The medium dose of ECC-JHF and pirfenidone were similar in improving pulmonary fibrosis in rats. In the TGF-β-induced lung fibroblast activation, ECC-JHF inhibited fibroblast activation by downregulating the levels of fibronectin, alpha-smooth muscle actin (α-SMA), and collagen I. Additionally, ECC-JHF upregulated the level of Nrf2 and its target proteins, including HO-1 and NQO1, as well as mitophagy-related proteins PINK1, PARK2, and LC3B. This led to an increase in the co-localization of TOM20 and LC3, thereby enhancing mitochondrial autophagy. The application of Nrf2 siRNA and Nrf2 inhibitors significantly diminished the effects of ECC-JHF on Nrf2 signaling, PINK1/PARK2-mediated mitophagy, and fibroblast activation. ECC-JHF exerts a protective effect against PF by suppressing fibroblast activation through the upregulation of Nrf2 and PINK1/PARK2-mediated mitophagy, it provides a new target and strategy for the treatment of pulmonary fibrosis.